«Save the Man». In way of documentary and exhibition project - Yu. Z. Kantor (Омский научный вестник: Серия "Общество. История. Современность")
The article is dedicated to the life and fate of a doctor, a graduate of the Omsk Medical Institute Andrei Pantyukhov — a man whom the famous writer Varlam Shalamov considered his friend and savior. Dr. Pantyukhov — the prototype of the protagonist of several «Kolyma Tales» by Shalamov. The article, thanks to documents from the Pantyukhov family archive, the archives of the Federal Security Service of Russia in the Omsk Region and the Ministry of Internal Affairs of Russia in the Magadan Region, the Historical Archive of the Omsk Region and the archive of the Omsk State Medical University, for the first time put into scientific circulation, makes it possible to find out the details of the biography of Pantyukhov, who devoted himself to serving the most humane from professions